PAI Teachers' Challenges in the Concept of Digital Transformation in the Era of Society 5.0. - Mulyana, Asep; Oktaviani, Rizki; Khairunnisa, Ririn; Rosinah, Rosinah; Indriawati, Intan (International Journal Labs, 2023)
Changes in the era of digital society 5.0 as a continuation of the development of the industrial revolution 4.0 have an impact on all lines of life including the education sector. Educators have major obstacles in dealing with Industry 4.0 and society 5.0, therefore an Islamic religious education teacher must carry out various active, innovative and creative learning strategies to enter the scope of digital society 5.0 transformation in the learning process. One of them is by changing the paradigm of thinking about the concept of Islamic learning, and being willing to accept new things that can support the acceleration of students' understanding of religious objects. This research is library research with an in-depth discussion of the contents of written or printed information in the mass media in order to produce a conclusion regarding the challenges of PAI teachers in the concept of transformation in the era of society 5.0. The purpose of this study is to find out and analyze how the challenges of PAI teachers are in the concept of digital transformation in the era of society 5.0. The results of this study are that in facing the challenges of PAI teachers in the concept of digital transformation in the era of society 5.0, a teacher must be literate and understand various types of technological media that can be applied in the learning process. For example, by delivering content material with E-learning such as Zoom, Google Meet, Google Classroom.